PROTECTIVE EFFECT OF GLYCOWITHANOLIDES ON SUBMANDIBULAR GLANDS OF D-GALACTOSE STRESSED MICE - R. N. MOTE; M. M. PILLAI; B. K. PAWAR (The Bioscan, 2010)
The study was undertaken to evaluate the effect of glycowithanolides (WSG) on the structure of submandibular gland of aging mice. The aging was induced by 5% D-galactose. Adult male mice (Mus musculus) were divided into main two group viz. protective and curative group. Each group further divided into four batches viz. (A) control batch, received 0.5mL 0.9% saline per day, (B) D-galactose stressed batch, received 0.5mL 5% D-galactose per day, (C) centrophenoxine treated batch, received 0.5mL centrophenoxine in 0.9% saline per day (80 mg / kg body weight), and (D) glycowithanolides treated batch, received 0.5 ml WSG per day (20 mg / kg body weight). Histological study of submandibular gland showed loss of structural integrity of acinar cells as well as GCT cells, irregular nuclear distribution, vacuolated cytoplasm in D-galactose stressed mice. Significant structural recovery was observed in antioxidant treatment, increase in size of acinar cells as well as GCT was observed in centrophenoxine and WSG treatment. Structural recovery was more pronounced in WSG treatment than centrophenoxine.